Weak hand preference in children with Down syndrome is associated with language deficits - Groen, M; Yasin, I; Laws, G; Barry, J; Bishop, D (Wiley, 2008)
This study explores associations between language ability and hand preference in children with Down syndrome. Compared to typically developing children of the same age, children with Down syndrome showed weaker hand preference, were less consistent in the hand they used and also less willing to reach to extreme positions in contralateral space. Within the group of children with Down syndrome, those who showed a stronger or more consistent hand preference had better language and memory skills. This association could not be explained by differences in non-verbal cognitive ability or hearing loss. These findings are discussed within the theory of neurolinguistic development proposed by Locke [Locke (1997). Brain & Language, 58, 265-326.